Pelatihan Manajemen Keuangan bagi UMKM "Kelompok Binaan Handayani Catering" di Tengah Covid 19 - Ahmad Rudi Yulianto; Wahyu Setiawan (Jurnal Surya Masyarakat, 2021)
MSMEs are an economic driving sector that can contribute greatly to the Indonesian economy. One of the weaknesses of MSMEs is that they still lack knowledge and understanding of financial management, especially when coupled with the Covid-19 epidemic, MSMEs are experiencing various problems, so there needs to be strengthening of MSMEs through various skills so that MSMEs can survive during pandemics and post-pandemics. One of the business groups that is quite affected by Covid-19, is MSMEs engaged in the culinary or food sector, which are indicated to still have weaknesses in the financial aspect. Our MSME partners in community service are handayani catering assisted groups. The PKM team makes efforts to assist the assisted catering groups through mentoring, empowerment and capacity building activities in financial management, starting with providing financial records and bookkeeping as well as various ways to mitigate financial risk. The result of this activity was that the participants began to prepare financial reports and began to implement financial management, especially cash flow, which was previously less of a concern. Participants were greatly helped by the preparation of financial reports as an indicator of business sustainability and health.